2021
DOI: 10.1111/jocs.15831
|View full text |Cite
|
Sign up to set email alerts
|

The fate of the left subclavian artery in TEVAR for aortic arch pathology

Abstract: Background and aim of study: The origin of the vertebral artery (VA) from the left subclavian (LSA) is variable and must be considered when proximal ligation or embolization is performed post thoracic endovascular aortic repair (TEVAR) and extraanatomical bypass (EAB). A retrospective study was conducted to understand the patency of the LSA and VAs after TEVAR and the relationship of the EAB to the LSA. Methods: Fifty-six patients underwent TEVAR where the LSA origin was occluded. A comparison was performed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Consequently, the LSA opening is occluded, or the chimney technique is performed. 25 During the follow-up period, we found that stent stenosis and entry flow from disconnected stents was more common in the ISFs group than in the CSs group. In the CSs approach, the branch and main stent grafts were integrated and well anastomosed.…”
Section: Valuablesmentioning
confidence: 77%
See 1 more Smart Citation
“…Consequently, the LSA opening is occluded, or the chimney technique is performed. 25 During the follow-up period, we found that stent stenosis and entry flow from disconnected stents was more common in the ISFs group than in the CSs group. In the CSs approach, the branch and main stent grafts were integrated and well anastomosed.…”
Section: Valuablesmentioning
confidence: 77%
“…Conversely, when in situ fenestration fails or the angle is unsatisfactory, we cannot retract the stent. Consequently, the LSA opening is occluded, or the chimney technique is performed 25 …”
Section: Discussionmentioning
confidence: 99%
“…Fewer than 10% of patients require an extremity intervention. 2 , 3 However, an aberrant right subclavian artery (RSA) is a rare anatomic variant (0.16%-2%) that complicates aortic repair. 4 , 5 In this variant, the RSA exits the descending aorta, usually in zone IV, and routinely requires endograft coverage, decreasing the perfusing pressures to the aforementioned collateral beds.…”
mentioning
confidence: 99%